2021
DOI: 10.3389/fpsyt.2021.529361
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of Deliberate Self-Harm Among Migrant Trauma-Affected Subgroups

Abstract: Introduction: Studies have shown that exposure to potentially traumatic events (PTEs) during the migration process has serious consequences on mental health. Migrants with a history of PTEs are more likely to inflict deliberate self-harm (DSH), a spectrum of behavior that includes non-suicidal self-injury (NSSI). With reference to a nonclinical sample of trauma-exposed migrants, this study aims to explore the prevalence of DSH and to assess the association with sociodemographic characteristics and clinical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Research shows that refugees face a higher risk of self-harm due to a mix of pre-migration trauma, like violence and persecution, and post-migration challenges, such as asylum uncertainty, cultural adjustment issues, and economic instability [ 15 , 16 ]. A study in Italy showed the prevalence of self-harm in this demographic to be 26.6% [ 17 ]. Common mental health problems among refugees, including depression, anxiety, and PTSD, increase the likelihood of self-harm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that refugees face a higher risk of self-harm due to a mix of pre-migration trauma, like violence and persecution, and post-migration challenges, such as asylum uncertainty, cultural adjustment issues, and economic instability [ 15 , 16 ]. A study in Italy showed the prevalence of self-harm in this demographic to be 26.6% [ 17 ]. Common mental health problems among refugees, including depression, anxiety, and PTSD, increase the likelihood of self-harm.…”
Section: Introductionmentioning
confidence: 99%
“…Common mental health problems among refugees, including depression, anxiety, and PTSD, increase the likelihood of self-harm. Additionally, difficulties in accessing mental health care, including language barriers, stigma, and the absence of culturally sensitive services, further heighten their vulnerability [ 17 19 ]. In addition, the refugee populations are encompassed in severe economic challenges, like limited job opportunities and financial instability that increase their chances of despair and having chronic thoughts of preferring to die [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…PTSD is prone to comorbid with many mental problems, such as sleep disorders, depressive disorders, and anxiety disorders ( 10 ). Timely interventions for patients with PTSD can reduce distress, which can help to reduce the occurrence of NSSI ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…elf-harm or self-injury is seen as a way for dealing with emotional problems, anger, depression, and distress [1]. Deliberate selfharm is defined as the intentional direct and indirect harm the self [2]. It is a behavior that causes minor or severe physical injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is a behavior that causes minor or severe physical injury. For example, trying to burn oneself, head banging, jumping from high places, poisoning oneself without attempting suicide [1], cuting/scratching the skin, and preventing wounds from healing [2]. Self-harm behavior is a wrong way to cope with psychological distress.…”
Section: Introductionmentioning
confidence: 99%